2017
DOI: 10.1016/j.mod.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Wnt signaling balances specification of the cardiac and pharyngeal muscle fields

Abstract: Canonical Wnt/β-catenin (Wnt) signaling plays multiple conserved roles during fate specification of cardiac progenitors in developing vertebrate embryos. Although lineage analysis in ascidians and mice has indicated there is a close relationship between the cardiac second heart field (SHF) and pharyngeal muscle (PM) progenitors, the signals underlying directional fate decisions of the cells within the cardio-pharyngeal muscle field in vertebrates are not yet understood. Here, we examined the temporal requireme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…However, although cardiac cell fate diversification has been elegantly studied via clonal analysis (Meilhac et al, 2003;Lescroart et al, 2010;Devine et al, 2014), how the magnitude of contribution to the developing heart from the CPC pool is regulated remains poorly understood. This process has perhaps been most examined in SHF progenitors, where several signaling pathways have been implicated in regulating the balance of CPC maintenance/proliferation and differentiation (Prall et al, 2007;Ryckebusch et al, 2008;Sirbu et al, 2008;Tirosh-Finkel et al, 2010;Zhao et al, 2014;Li et al, 2016;Mandal et al, 2017). Notable among these are fibroblast growth factor (FGF) and retinoic acid (RA) signaling, the balance of which fine-tunes the specification and differentiation of cardiac progenitors (Ilagan et al, 2006;Park et al, 2008;Rochais et al, 2009;Sorrell and Waxman, 2011;Witzel et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, although cardiac cell fate diversification has been elegantly studied via clonal analysis (Meilhac et al, 2003;Lescroart et al, 2010;Devine et al, 2014), how the magnitude of contribution to the developing heart from the CPC pool is regulated remains poorly understood. This process has perhaps been most examined in SHF progenitors, where several signaling pathways have been implicated in regulating the balance of CPC maintenance/proliferation and differentiation (Prall et al, 2007;Ryckebusch et al, 2008;Sirbu et al, 2008;Tirosh-Finkel et al, 2010;Zhao et al, 2014;Li et al, 2016;Mandal et al, 2017). Notable among these are fibroblast growth factor (FGF) and retinoic acid (RA) signaling, the balance of which fine-tunes the specification and differentiation of cardiac progenitors (Ilagan et al, 2006;Park et al, 2008;Rochais et al, 2009;Sorrell and Waxman, 2011;Witzel et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…the right ventricle and outflow tract) share a common origin with branchiomeric head muscles, in the cardiopharyngeal mesoderm of the early embryo (Diogo et al, 2015a;Gopalakrishnan et al, 2015;Harel et al, 2012;Lescroart et al, 2010Lescroart et al, , 2014Lescroart et al, , 2015Mandal et al, 2017;Nathan et al, 2008;Tirosh-Finkel et al, 2006;Tzahor and Evans, 2011) .…”
Section: Introductionmentioning
confidence: 99%
“…The cellular and molecular characteristics of multipotent cardiopharyngeal progenitors, and the mechanisms underlying the early heart vs. pharyngeal/branchiomeric muscle fate choices remain largely elusive, and studies are partially hindered by the complexity of early vertebrate embryos (Chan et al, 2016;Mandal et al, 2017) . Single cell approaches thus offer an opportunity to uncover the molecular underpinnings of early cardiopharyngeal development.…”
Section: Introductionmentioning
confidence: 99%
“…In fish, tbx1 is also required to specify the nkx2.5+ CPF. Moreover, recent studies have also shown a role for Wnt signaling in the balance between cardiac and skeletal muscle lineages, as Wnt activation during or prior to gastrulation inhibits pharyngeal muscle specification at the expense of cardiac lineages (Mandal et al 2017). Such a role for Wnt has not been found in tunicates (Kaplan et al 2019).…”
Section: Cardiomyocyte Versus Skeletal Muscle Fatementioning
confidence: 99%